Dialects in the Chukchi language - Ranavrol’tyn, Grigori (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThis research note briefly describes a linguistic research project initiated in 2007 on the description of current dialects in the Chukchi language